Comparative effectiveness of antibiotic therapy for carbapenem-resistant Enterobacterales (CRE) bloodstream infections in hospitalized US veterans. Issue 5 (26th October 2022) - Wilson, Geneva M; Fitzpatrick, Margaret A; Suda, Katie J; Smith, Bridget M; Gonzalez, Beverly; Jones, Makoto; Schweizer, Marin L; Evans, Martin; Evans, Charlesnika T
Abstract: Background: Carbapenem-resistant Enterobacterales bloodstream infections (CRE-BSI) increase mortality three-fold compared with carbapenem-susceptible bloodstream infections. Because these infections are rare, there is a paucity of information on mortality associated with different treatment regimens. This study examines treatment regimens and association with in-hospital, 30 day and 1 year mortality risk for patients with CRE-BSI. Methods: This retrospective cohort study identified hospitalized patients within the Veteran Affairs (VA) from 2013 to 2018 with a positive CRE blood culture and started antibiotic treatment within 5 days of culture. Primary outcomes were in-hospital, 30 day and 1 year all-cause mortality. Secondary outcomes were healthcare costs at 30 days and 1 year and Clostridioides difficile infection 6 weeks post culture date. The propensity for receiving each treatment regimen was determined. Multivariable regression assessed the association between treatment and outcomes. Results: There were 393 hospitalized patients from 2013 to 2018 included in the study. The cohort was male (97%) and elderly (mean age 71.0 years). Carbapenems were the most prescribed antibiotics (47%). In unadjusted analysis, ceftazidime/avibactam was associated with a lower likelihood of 30 day and 1 year mortality. After adjusting, ceftazidime/avibactam had a 30 day mortality OR of 0.42 (95% CI 0.17–1.02). No difference was found in C. difficile incidence at 6 weeks post-infection or total costs at 30 days or 1 year post culture date by any treatments. Conclusions: In hospitalized veterans with CRE-BSI, none of the treatments were shown to be associated with all-cause mortality. Ceftazidime/avibactam trended towards protectiveness against 30 day and 1 year all-cause mortality. Use of ceftazidime/avibactam should be encouraged for treatment of CRE-BSI.